2023
DOI: 10.3389/fphar.2023.1112123
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of soluble guanylate cyclase by vericiguat reduces skeletal muscle atrophy of mice following chemotherapy

Abstract: Background: The chemotherapeutic doxorubicin (DOX) promotes severe skeletal muscle atrophy, which induces skeletal muscle weakness and fatigue. Soluble guanylate cyclase (sGC) contributes to a variety of pathophysiological processes, but whether it is involved in DOX-induced skeletal muscle atrophy is unclear. The present study aimed to stimulate sGC by vericiguat, a new oral sGC stimulator, to test its role in this process.Methods: Mice were randomly divided into four groups: control group, vericiguat group, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In the VICTORIA trial, vericiguat demonstrated its safety in heart failure patients, reducing cardiovascular death or heart failure hospitalization [27,28]. Vericiguat's vasodilatory effects can help enhance blood flow to skeletal muscle, potentially improving its function and reducing symptoms such as exercise intolerance or sarcopenia [29]. Recent cellular and preclinical studies indicate the beneficial effects of guanylate cyclase on muscle cell survival and prevention of sarcopenia, leading to the potential benefits of pharmacological guanylate cyclase stimulators in muscle loss prevention and treatment [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…In the VICTORIA trial, vericiguat demonstrated its safety in heart failure patients, reducing cardiovascular death or heart failure hospitalization [27,28]. Vericiguat's vasodilatory effects can help enhance blood flow to skeletal muscle, potentially improving its function and reducing symptoms such as exercise intolerance or sarcopenia [29]. Recent cellular and preclinical studies indicate the beneficial effects of guanylate cyclase on muscle cell survival and prevention of sarcopenia, leading to the potential benefits of pharmacological guanylate cyclase stimulators in muscle loss prevention and treatment [30,31].…”
Section: Introductionmentioning
confidence: 99%